2012
DOI: 10.3345/kjp.2012.55.4.121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in random blood glucose and body mass index during and after completion of chemotherapy in children with acute lymphoblastic leukemia

Abstract: PurposeImproved survival of patients with childhood acute lymphoblastic leukemia (ALL) has drawn attention to the potential for late consequences of previous treatments among survivors, including metabolic syndrome. In this study, we evaluated changes in 3 parameters, namely, random blood glucose, body mass index (BMI), and Z score for BMI (Z-BMI), in children with ALL during chemotherapy and after completion of treatment.MethodsPatients newly diagnosed with ALL from January, 2005 to December, 2008 at Saint Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Again, the elimination of cranial irradiation in many patients may aid in minimizing these toxicities. In our study of patients treated with dexamethasone-based chemotherapy and without cranial irradiation, random glucose and body mass index decreased significantly at 12 months posttreatment completion compared to values measured during chemotherapy76). Although limited by short-term follow-up, our study did not find evidence for either long-term glucose intolerance or potential obesity during the aftermath of therapy for patients treated without allogeneic HCT and cranial irradiation.…”
Section: Long-term Effects Of Treatmentcontrasting
confidence: 70%
“…Again, the elimination of cranial irradiation in many patients may aid in minimizing these toxicities. In our study of patients treated with dexamethasone-based chemotherapy and without cranial irradiation, random glucose and body mass index decreased significantly at 12 months posttreatment completion compared to values measured during chemotherapy76). Although limited by short-term follow-up, our study did not find evidence for either long-term glucose intolerance or potential obesity during the aftermath of therapy for patients treated without allogeneic HCT and cranial irradiation.…”
Section: Long-term Effects Of Treatmentcontrasting
confidence: 70%
“…Sixteen studies provided data for mean and SD of BMI z‐score or percentile for at least two time points during and after treatment and were included in the meta‐analysis (Table ). Baseline BMI z‐scores ranged from −0.64 to 0.64 across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 included studies, eight [] explicitly reported the mean BMI z‐score for the overall cohort, one reported the mean BMI percentile, which was converted to BMI z‐score based on the standard normal curve, and we obtained the mean BMI z‐score directly from authors in one study . For the remaining six studies, the mean BMI z‐score was calculated as a weighted average based on subgroup values (using sample size as weights) in five studies , or was estimated based on median BMI z‐score in one study .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%